Back to the future: Comparing Yeast as an outmoded artificial Tracer for simulating microbial transport in Karst aquifer systems to more modern approachs - O'Connell, David; Coxon, Catherine; Gill, Laurence (My University, 2024)
Bacterial contamination of karst groundwater is a major concern for public health. Artificial tracing studies are crucial for establishing links between locations where pollutants can rapidly reach the aquifer systems and subsequent receptors, as well as for enhanced understanding of pollutant transport. However, widely used solute artificial tracers do not always move through the subsurface in the same manner as particles and microorganisms, hence may not be ideal proxies for predicting movement of bacterial contaminants. This study evaluates whether a historically used microbial tracer (yeast) which is readily available, inexpensive, and environmentally friendly, but usually overlooked in modern karst hydrogeological studies due to challenges associated with its detection and quantification in the past, can reemerge as a valuable tracer using the latest technology for its detection. Two field-based studies on separate karst systems were carried out during low-flow conditions using a portable particle counter along with flow cytometry measurements to monitor the recovery of the yeast at the springs. Soluble fluorescent dyes were also injected simultaneously with the yeast for comparison of transport dynamics. On one tracer test, through a karst conduit of much higher velocities, the injected yeast and fluorescent dye arrived at the same time at the spring, in comparison to the tracer test on a conduit system with lower groundwater velocities in which the yeast particles were detected before the dye at the sampling site. Both a portable particle counter and flow cytometry successfully detected yeast during both tests, thereby demon- strating the applicability of this tracer with contemporary instrumentation. Even though no significant advan- tages of flow cytometry over the portable counter system can be reported on the basis of the presented results, this study has shown that flow cytometry can be successfully used to detect and quantify introduced microbial tracers in karst environments with extremely high precision.
PUBLISHED
Keywords: Artificial tracer; Microbial transport; Karst aquifer; Yeast; Flow cytometry; Particle counter; Creative Technologies; International Development; International Integration; Nanoscience & Materials; Smart & Sustainable Planet; Environmental engineering; GROUNDWATER; karst hydrogeology; water tracing